Perfil epidemiológico de saúde de pacientes atendidos no estágio de fisioterapia ortopédica do ISB-UFAM em Coari-AM - Silva, Gabriel Carvalho da (Brasil, 2024)
Introduction: More and more individuals are affected by orthopedic pathologies. These changes cause loss of function and functional limitation. Some individuals are assisted by the free Orthopedic Physical Therapy services in public universities. Objective: To describe the epidemiological health profile of patients treated in the Orthopedic Physical Therapy internship at ISB-UFAM. Materials and Methods: Retrospective cross-sectional study with a quantitative approach carried out with data from the records of patients in the Orthopedic Physical Therapy internship at ISB-UFAM between the years 2022 and 2024. Results: 191 patient records from the period 2022 to 2024 were analyzed, and 2 evaluation forms were excluded from this study, as not all the data were complete, thus not meeting the eligibility criteria. Of these, 78 were male and 111 female. The mean age of the patients was 44.2 years. In 2022, the most affected region in the patients treated was the lumbar with 12 cases, in 2023 it was the knee with 12 cases and in 2024 the most affected region was the knee with 32 cases. Conclusion: The data point to the vulnerability of the aforementioned areas to injuries, especially in populations exposed to biomechanical overloads, and reinforce the need for public policies for the prevention and treatment of orthopedic diseases.